Sequestosome‐1 (p62) expression reveals chaperone‐assisted selective autophagy in immune‐mediated necrotizing myopathies. (27th August 2019) - Fischer, Norina; Preuße, Corinna; Radke, Josefine; Pehl, Debora; Allenbach, Yves; Schneider, Udo; Feist, Eugen; von Casteleyn, Vincent; Hahn, Katrin; Ruck, Tobias; Meuth, Sven G.; Goebel, Hans‐Hilmar; et al.
Abstract: Diffuse myofiber necrosis in the context of inflammatory myopathy is the hallmark of immune‐mediated necrotizing myopathy (IMNM). We have previously shown that skeletal muscle fibers of IMNM patients may display nonrimmed vacuoles and sarcoplasmic irregularities. The dysfunctional chaperone activity has been linked to the defective assembly of skeletal muscle proteins and their degradation via lysosomes, autophagy and the proteasomal machinery. This study was undertaken to highlight a chaperone‐assisted selective autophagy (CASA) pathway, functionally involved in protein homeostasis, cell stress and the immune response in skeletal muscle of IMNM patients. Skeletal muscle biopsies from 54 IMNM patients were analyzed by immunostaining, as well as by q PCR. Eight biopsies of sIBM patients served as pathological controls, and eight biopsies of nondisease control subjects were included. Alteration of autophagy was detectable in all IMNM biopsy samples highlighted via a diffuse sarcoplasmic staining pattern by p62 and LC3 independent of vacuoles. This pattern was at variance with the coarse focal staining pattern mostly confined to rimmed vacuoles in sIBM. Colocalization of p62 with the chaperone proteins HSP70 and αB‐crystalline points to the specific targeting of misfolded proteins to the CASA machinery. Bcl2‐associated athanogene 3 (BAG3) positivity of these fibers emphasizes the selectivity of autophagy processes and these fibers also express MHC class I sarcolemma. Expression of genes involved in autophagy and endoplasmic reticulum (ER) stress pathways studied here is significantly upregulated in IMNM. We highlight that vacuoles without sarcolemmal features may arise in IMNM muscle biopsies, and they must not be confounded with sIBM‐specific vacuoles. Further, we show the activation of selective autophagy and emphasize the role of chaperones in this context. CASA occurs in IMNM muscle, and specific molecular pathways of autophagy differ from the ones in sIBM, with p62 as a unique identifier of this process.